Regional analysis of segmented-macular structure in patients with myopic anisometropia - KIRIK, FURKAN; KIRIK, FURKAN; EKİNCİ, CANSU; EKİNCİ, CANSU; AKBULUT, ERSİN; AKBULUT, ERSİN; BAYRAKTAR, HAVVANUR; BAYRAKTAR, HAVVANUR; Ozdemir, Hakan; ÖZDEMİR, MEHMET HAKAN (My University, 2021)
Purpose To compare intraretinal layers between the eyes in patients with myopic anisometropia, and evaluate the relationship between the layers with spherical equivalent (SE) and axial length (AL). Methods In this retrospective study, the more myopic (MM) and fellow (F) eyes of 41 patients with myopic anisometropia, and 38 emmetropic (+/- 0.50 diopter) control (C) eyes were inclueded. Intraretinal layer segmentation was performed by optical coherence tomography. Global volumes of retinal layers and their thicknesses in nine macular regions were compared. Correlation analysis was used to determine the relationship with SE and AL in each layer. Results Total retinal, ganglion cell (GCL), inner nuclear (INL), and outer plexiform (OPL) layer volumes in MM eyes were less than in C eyes, while INL and OPL were less than in F eyes. There was no difference in the fovea, except for the retinal pigment epithelium. In MM eyes, only INL and OPL were thin in at least one perifoveal and parafoveal quadrant compared to F eyes. Only INL and OPL thicknesses were significantly correlated with both SE and AL in all perifoveal quadrants. In contrast to the thinning found in MM eyes, the only layer in which thickening was detected to compare to C eye was nerve fiber layer (NFL), which correlated positively with SE and negatively with AL. Conclusion While the fovea is less affected by myopia, thinning becomes remarkable in the perifoveal quadrants. Despite thinning in many layers, especially INL and OPL, NFL thickening may be seen due to myopia.